Spatial development, power dynamics and social tensions: Insights from Dwesa-Cwebe, Wild Coast Region, South Africa - Tafadzwa Mambiravana; Elmon Mudefi (Town and Regional Planning)
Spatial development remains a priority in South Africa and is central to the Spatial Planning and Land Use Management Act (SPLUMA), the Spatial Development Framework (SDF), and broader National Development Plans (NDPs). However, there has been limited focus in literature on the need to address power imbalances in development processes, which not only hinder progress, but also encourage social tensions. This is evident in Dwesa-Cwebe on the Wild Coast, South Africa, which, due to the legacies of apartheid policies, remains marginalised and subjected to external control over development. Without a consensus on the inherent power imbalances and the resulting social conflicts in this community, implementing SPLUMA, SDFs, and NDPs will remain challenging, as has been the case since the advent of democracy in South Africa. This study explores the interaction of power dynamics and their impact on spatial development in Dwesa-Cwebe. Employing a qualitative research design, data were collected from 101 participants through focus group discussions (FGDs) and interviews with government representatives, ward councillors, traditional authorities, and community members. The research revealed significant power imbalances in the implementation of spatial development initiatives, with the government dominating the process while marginalising input from other stakeholders. These imbalances were found to be a key driver of social tensions and delays in the execution of SPLUMA, SDFs, NDPs, and other regional development policies. The study recommends interdisciplinary, gender-inclusive policies that incorporate monitoring and feedback mechanisms to ensure continuous improvement.